DEM modeling of cantilever retaining excavations: Implications for lunar constructions. Issue 2 (18th April 2016) - Jiang, Mingjing; Shen, Zhifu; Utili, Stefano
Abstract : Purpose: – Retained excavation is important for future lunar exploratory missions and potential human colonization that requires the construction of permanent outposts. Knowledge in excavation obtained on the earth is not directly applicable to lunar excavation because of the low lunar gravity and the non-negligible adhesive van der Waals interactions between lunar regolith grains. The purpose of this paper is to reveal how the gravity level and lunar environment conditions should be considered to extend the knowledge in earth excavation response to lunar excavation. Design/methodology/approach: – Two-dimensional discrete element method simulations were carried out to investigate the respective effect of gravity level and lunar environment conditions (high-vacuum and extreme temperature) on retained excavation response. A novel contact model was employed with a moment – relative rotation law to account for the angularity of lunar soil particles, and a normal attractive force to account for the van der Waals interactions. Findings: – The simulation results showed that the excavation response is non-linearly related to the gravity level. Van der Waals interactions can increase the dilatancy of lunar regolith and, surprisingly as a consequence, significantly increase the bending moment and deflection of the retaining wall, and the ground displacements. Based on the simulation results, a parabola model was proposed to predict the excavation-induced lateral ground movements on the moon. Originality/value: – This study indicates that an unsafe estimate of the wall response to an excavation on the moon would be obtained if only the effect of gravity is considered while the effect of van der Waals interactions is neglected.